The lived experience of sport-related concussion: A collaborative inquiry in elite sport - Seguin, C. M.; Culver, D. M. (Journal of Applied Sport Psychology, 2022)
Sport-related concussion(s) (SRCs) pose a complex problem to researchers and practitioners alike. The psychological and emotional experience of these injuries requires individualized and multidisciplinary intervention to promote wellbeing and effective recovery. These interventions require a thorough understanding of the SRC experience. Thus, collaborative inquiry, a novel approach in the SRC domain, was employed to give athletes a voice in how their experience is portrayed and understood within the research and applied communities. Data were generated over two years through on-going discussion and reflection between the researchers and twelve elite athletes who experienced SRCs. Athletes advocated for a broader view of their injury that considers the interplay of sociocultural factors and the individual`s psychosocial experience. Mutual engagement through interviews, member reflections, focus groups, follow-up emails, and further reflective conversations generated two composite narratives. These narratives are interpreted using Bronfenbrenner`s Ecological Systems Theory to underline the interplay of factors: (1) microsystem (athletic identity), (2) mesosystem ((dis)trust in relationships), (3) exosystem (concussion protocols), (4) macrosystem (sport culture), and (5) chronosystem (timing related to major events and recovery). Through this unique combination of methodology and theory within SRC research, we aim to highlight opportunities for applied intervention, multidisciplinary collaboration, and future scientific exploration